Airway geometry, airway flow, and particle measurement methods: implications on pulmonary drug delivery. (4th March 2018) - Kourmatzis, A.; Cheng, S.; Chan, H.-K.
ABSTRACT: Introduction : The effectiveness of drug delivery to the lungs is inextricably linked to the fundamental interactions that occur between particles and flow in the extrathoracic airway. Research in this field requires time resolved in-vivo and in-vitro measurements of three separate, yet intricately linked parameters: i) airway flow, ii) airway geometry, and iii) drug particle characteristics. A number of recent significant developments have been made in the experimental diagnostic tools used to characterise these parameters. Areas covered : In this review paper, we summarize the key recent findings that have resulted from the implementation of laser and optical diagnostic tools towards characterization of airway flow, extrathoracic airway geometry and drug particle characteristics. These three areas are discussed together, enabling a critical review of the implications of recent experimental findings on likely future developments in drug delivery to the lungs. Expert opinion : Improvements in drug delivery systems will result through implementation of laser and optical based diagnostic methods that can spatially and temporally resolve particle and agglomerate shape, size and dynamic characteristics. Design of inhaler devices must be done in parallel to developing realistic in-vitro upper airway replicas that account for physiological differences between patient groups, as a function of respiratory disease severity.